Medically Important Coagulase Negative Staphylococci - Vanaparthi, Nagaraju; Sadawarte, Kalpana (International Journal of Clinical and Biomedical Research, 2019)
In recent years, coagulase negative Staphylococci (CONS) are increasingly recognized as one of the major causes of health care associated infections (HCAI). CONS infections are one of the major causes of morbidity and mortality in hospitalized patients. As CONS colonize various parts of the skin and mucous membranes, most of infections are endogenous in origin. However, they are also transmitted exogenously via various medical/ surgical procedures. The aim of present review article is to update and summarize the information available on medically important CONS with special reference to epidemiology, laboratory diagnosis and antibiotic resistance.